Mitochondrial depletion syndrome type 3: the Lebanese variant - Majdalani, Marianne; Yazbeck, Nadine; El Harake, Lamis; Samaha, Jinane; Karam, Pascale E. (Frontiers in Genetics, 2023)
Mitochondrial DNA depletion syndrome type 3 is an emerging disorder linked to variants in the deoxyguanosine kinase gene, encoding for mitochondrial maintenance. This autosomal recessive disorder is frequent in Middle East and North Africa. Diagnosis is often delayed due to the non-specificity of clinical presentation with cerebro-hepatic deterioration. The only therapeutic option is liver transplantation, although still debatable.We describe the clinical, biochemical and molecular diagnosis of Lebanese patients with this rare disorder. A review of all cases from Middle East and North Africa is also performed.All Lebanese patients share a unique mutation, unreported in other populations. Almost half of the patients worldwide originate from Middle East and North Africa, reported from 7 countries only out of 21 in this region. Clinical presentation is heterogeneous with early onset neurological and hepatic signs. Liver failure and lactic acidosis are constant. Several variants are identified in each population; A unique c.235C>T p.(Gln79*) pathogenic variant is found in Lebanese patients. Outcome is poor with death before 1 year of age.The pathogenic, nonsense variant c.235C>T p.(Gln79*) in the deoxyguanosine kinase gene may be considered a founder mutation in Lebanon. Further genotypic delineation of this devastating disorder in populations with high consanguinity rates is needed.